6th Annual Fresno County Young Lawyers Association Justice Hopper Memorial Luncheon; Speaker: San Francisco Superior Court Judge Ira Brown - Watkins, Howard::::::::: (1987)
Justice Donald Franson introducing keynote speaker San Francisco Superior Court Judge Ira Brown Seated: Howard Sagaser, Judge Brown and ?